Assessment of Monocyte Chemoattractant Protein -1 and Fertility Hormones in Iraqi Women with Polycystic Ovarian Syndrome - Ibrahim, Sara Khaleel; Sura Fouad Alsaffar (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Polycystic ovarian syndrome (PCOS) is a well-known endocrinopathy and one of the most frequent endocrine-reproductive-metabolic syndromes in women, which can result in reduced fertility. While the actual cause is unknown, PCOS is regarded as a complicated genetic characteristic with a great degree of variability. Moreover, hormones and immune cells, including both innate and acquired immune cells, are thought to interact in PCOS. Chronic low-grade inflammation raises the risk of autoimmune disease. The study’s purpose is to investigate the chemokine monocyte chemoattractant protein-1 (MCP-1) and fertility hormones in samples of women patients with polycystic ovary syndrome (PCOS) in the City of Medicine. Sixty PCOS women comprise 30 healthy control women; their average age was 20–40 years, and their weight ranged from 60 to 100 kg. The results showed an increase in the level of MCP1 in PCOS patients, but this increase was not significant (P<0.05), which was not influenced by BMI or fertility hormones. As well as elevated fertility hormones, this study, when compared to controls as well as patients with PCOS, showed a significant increase in the level of testosterone (14.63 ±2.30 nmol/L) while in control women (0.627 ±0.04), LH hormone in patients and control group (6.54 ±0.51 mIU/mL), and 2.93 ±0.18, respectively. Prolactin hormone was increased in PCOS patients (16.27 ±1.25 ng/mL) when compared to the control group (12.85 ±0.62). There was no significant difference in FSH hormone in women with PCOS (5.27 ±0.28 mIU/mL) compared with the control group (5.59 ±0.18).